The Analysis of Sustainable Construction Strategies on the Likupang Special Economic Zone (SEZ) - R. Arifuddin; R. U. Latief; S. Hamzah; D. Pangemanan; E. Aprianti; R. Fadlillah (Civil Engineering Journal, 2023)
Many challenges are faced in implementing sustainable construction in Indonesia. This research aims to find an effective method for adopting sustainable construction. The method used combines qualitative and quantitative methods by incorporating the identification of significant factors affecting the adoption of sustainable construction. In data collection with the SWOT system, FGDs and interviews provided accurate information regarding factors and strategies to promote sustainable construction, particularly in the Likupang SEZ Project. From the results of the study, the IFSC value for the promotion strategy of sustainable construction in the Likupang SEZ project is the social factor of 0.2, followed by the economic factor of 0.3, the environmental factor of 1.2, and the government support factor, business investment, and cultural factors of 1.4, respectively. The highest IFSC value was obtained for the human resource factor of 1.6. Thus, it can be concluded that human resources must be accompanied by government support along with business investment and cultural influences in order to realize adequate sustainable development projections for the Likupang SEZ project in the future. Doi: 10.28991/CEJ-SP2023-09-07 Full Text: PDF